Step-by-step explanation:
puhhh ! that way of typing can be misleading.
let me sum up what equations I think the problem definition specified :
1)
6x + 2y = 82
x - y = 3
2)
y = 4x - 1
x + y = 9
3)
4x + 3y = 17
y = 5 - x
solving 1)
x - y = 3 => x = y + 3
putting this into the first equation
6×(y+3) + 2y = 82
6y + 18 + 2y = 82
8y +18 = 82
8y = 64
y = 8
x = y + 3 = 8 + 3 = 11
solving 2)
using the first equation in the second equation
x + (4x - 1) = 9
5x - 1 = 9
5x = 10
x = 2
y = 4x - 1 = 4×2 - 1 = 8 - 1 = 7
solving 3)
using the second equation in the first equation
4x + 3×(5 - x) = 17
4x + 15 - 3x = 17
x + 15 = 17
x = 2
y = 5 - x = 5 - 2 = 3